An experimental test of climate change effects in northern lakes: Increasing allochthonous organic matter and warming alters autumn primary production. (8th January 2021) - Hamdan, Mohammed; Byström, Pär; Hotchkiss, Erin R.; Al‐Haidarey, Mohammed J.; Karlsson, Jan
Abstract: Climate changes are predicted to influence gross primary production (GPP) of lakes directly through warming and indirectly through increased loads of allochthonous coloured dissolved organic matter (cDOM) from surrounding landscapes. However, few studies have investigated this combined effect. Here we tested the effects of warming (elevated 3℃) and cDOM input (three levels of humic river water addition) on GPP in autumn (2 months including open water and ice‐covered periods) in experimental pond ecosystems. The cDOM input decreased whole‐ecosystem GPP at natural temperature conditions mainly as a result of lower benthic GPP not fully counteracted by an increase in pelagic GPP, while warming increased whole‐ecosystem GPP due to a positive response of mainly pelagic GPP at all levels of cDOM input. Warming delayed autumn ice cover formation by 2 weeks but did not affect light availability in the water column compared to ambient ice‐covered treatments. Gross primary production during this period was still affected by warming and cDOM. The results stress the importance of accounting for multiple climate drivers and habitats when predicting lake GPP responses to climate change. We conclude that climate change may shift whole‐ecosystem GPP through different responses of habitat‐specific GPP to increasing cDOM inputs and warming.